2017
DOI: 10.1016/j.bbcan.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic basis of cancer health disparities: Looking beyond genetic differences

Abstract: Despite efforts at various levels, racial health disparities still exist in cancer patients. These inequalities in incidence and/or clinical outcome can only be explained by a multitude of factors, with genetic basis being one of them. Several investigations have provided convincing evidence to support epigenetic regulation of cancer-associated genes, which results in the differential transcriptome and proteome, and may be linked to a pre-disposition of individuals of certain race/ethnicity to early or more ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 173 publications
0
46
0
Order By: Relevance
“…Interestingly, PSPHL levels are relatively higher in AA breast tumors than the CA breast tumors [ 33 ]. Health disparities in breast cancer are well documented [ 34 , 35 ] and the study on PSPHL in breast tumors [ 33 ] identified partial deletion (30Kb long fragment) of chromosome 7p11 in CA women, which led to attenuation of expression of PSPHL in CA breast tumors. No such mechanism was proposed for observed disparate expression of PSPHL in OCs of AA vs. CA origin, and would be interesting to elucidate.…”
Section: Biological Basis Of Ovarian Cancer Health Disparitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, PSPHL levels are relatively higher in AA breast tumors than the CA breast tumors [ 33 ]. Health disparities in breast cancer are well documented [ 34 , 35 ] and the study on PSPHL in breast tumors [ 33 ] identified partial deletion (30Kb long fragment) of chromosome 7p11 in CA women, which led to attenuation of expression of PSPHL in CA breast tumors. No such mechanism was proposed for observed disparate expression of PSPHL in OCs of AA vs. CA origin, and would be interesting to elucidate.…”
Section: Biological Basis Of Ovarian Cancer Health Disparitiesmentioning
confidence: 99%
“…Epigenetic changes are known to function as liaisons between socioeconomic factors and the genome; they keep accumulating and affecting the epigenome in various racial/ethnic groups, resulting in disparate and poor cancer outcomes [ 35 ]. A functional role of epigenetic changes in aggressive high-grade serous OC has been described, leading to resistance against platinum-containing chemotherapy [ 53 ].…”
Section: Biological Basis Of Ovarian Cancer Health Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, AA patients with breast, head and neck, or endometrial cancer have higher levels of chromosomal instability and frequency of TP53 mutations and CCNE1 amplification than white patients. 17 Furthermore, race is a social construct and is often a proxy for chronic stressors that minority populations face, such as low socioeconomic status, Cancer February 15, 2020 poor access to health care, dangerous environments, and interpersonal discrimination. 15,16 Epigenetic differences are particularly relevant because they can be shaped by environmental factors, such as chronic stress, social interactions, and toxins.…”
Section: Introductionmentioning
confidence: 99%
“…15 Theses epigenetic changes can function as a liaison between social, cultural, and environment factors and the genome. 17 Furthermore, race is a social construct and is often a proxy for chronic stressors that minority populations face, such as low socioeconomic status, Cancer February 15, 2020 poor access to health care, dangerous environments, and interpersonal discrimination. 18 These unique stressors that a racial group experiences may affect their epigenome and ability to respond to disease, leading to poor outcome and response to therapy.…”
Section: Introductionmentioning
confidence: 99%